Theoretical and Legal and Economic Characteristics of Novellization of Taxation in Ukraine - ROSSIKHINA, Halyna V.; ROSSIKHIN, Vasyl V.; BARABASH, Tetyana O.; SHCHERBA, Viktoriia M.; SYDORENKO, Olha O. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).21, 2019)
Expressing the interests of society in various spheres of life, the state is building an appropriate policy – economic, social, legal, etc. One of the means of interaction between the object and the subject when achieving the objectives of state regulation is the combination of socio-economic processes, the development of the financial and credit mechanism. The financial system covers the relations for the accumulation and use of financial resources of the state, that is the budget and extrabudgetary funds. The main source of public revenues generation is taxes. That’s why at the present stage, tax reforms and transformations are uppermost in the processes of improvement of the market relations.